2002
DOI: 10.1073/pnas.022582899
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized complexity in economics and finance

Abstract: This article discusses some of the similarities between work being done by economists and by physicists seeking to contribute to economics. We also mention some of the differences in the approaches taken and seek to justify these different approaches by developing the argument that by approaching the same problem from different points of view, new results might emerge. In particular, we review two newly discovered scaling results that appear to be universal, in the sense that they hold for widely different eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…However, there is also a class of phenomena that follow a much different probability curve that has a very high probability at one end of the range of occurrences and very low at the other end. These power curve probabilities are often suggested for varying physical, natural, economic and social phenomena [75][76][77][78][79][80][81]. Examples of phenomena following a power distribution are earthquakes [75], the number of species in general [79], the use of words [77] and the distribution of wealth [82].…”
Section: Distance Decay and Power Curvesmentioning
confidence: 99%
“…However, there is also a class of phenomena that follow a much different probability curve that has a very high probability at one end of the range of occurrences and very low at the other end. These power curve probabilities are often suggested for varying physical, natural, economic and social phenomena [75][76][77][78][79][80][81]. Examples of phenomena following a power distribution are earthquakes [75], the number of species in general [79], the use of words [77] and the distribution of wealth [82].…”
Section: Distance Decay and Power Curvesmentioning
confidence: 99%
“…As a direct consequence of modulated redox/ROS dynamics, the aged cells up-regulate uncoupling protein homolog possibly for mitigating increased oxidative stress, which in turn contributes to diminished bioenergetics during substrate metabolism. Complex behaviors have been reported recently in various physiological signals such as heart beat intervals, gait dynamics, and respiratory signals, thus challenging the classical paradigm of homeostatic regulation (2,(7)(8)(9)(10)(11)(12)(13). Our data demonstrate for the first time that similar physiologically relevant nonlinear dynamical features are operative at the level of single cells for efficient regulation of energy metabolism.…”
mentioning
confidence: 61%
“…Complexity in a dynamic system is characterized by mutually interacting components (nonlinear network dynamics), hypersensitivity to initial conditions (deterministic chaos), and longterm memory processes (power-law scaling) (1,2). Because of the fact that multiple enzymes, cofactors, and signaling molecules contribute to efficient cell survival amid spatially/temporally varying stimuli, metabolic networks in a living cell are unique biological candidates for studying the role that complexity plays in regulatory enzyme kinetics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The financial market is naturally a complex system, and the economy and financial systems have a self-organized complexity [5]. Many studies have shown that complex networks have been successfully used to describe financial systems [6].…”
Section: Introductionmentioning
confidence: 99%